Produção e caracterização de filmes OSL baseados na fluorita natural brasileira - Oliveira, Pamella Nathielli Almeida de (2024)
The Optically Stimulated Luminescence (OSL) technique is widely used in radiation dosimetry. At the forefront of OSL detector development is the production of two-dimensional (2D) ûlms for radiation dose mapping. Among the advantages of this type of detector are spatial resolution, the possibility of dose reassessment, and reusability. This work developed a methodology for producing OSL ûlms based on Brazilian natural üuorite, composed almost exclusively of calcium üuoride (CaF 2 ). Aiming at the possible applications of OSL ûlms with different concentrations and granulometry of the radiation-sensitive material (fluorite crystals) . The different ûlms produced then had their dosimetric properties analyzed, and the protocol for reuse was established. Readings were performed on a Risø TL/OSL automated reader. The homogeneity of the different ûlms was measured by evaluating the variation in the OSL response of samples from different parts of the same ûlm exposed to the same dose at different times. Reproducibility was evaluated by considering the response of the same sample when exposed to the same radiation dose. Considering the coeýcients of variation and the initial and total signals, good homogeneity and reproducibility were obtained for all ûlms. It is worth mentioning that better homogeneity results were obtained when considering the initial signal and smaller grain size (coeýcient of variation of 2.7% and 8.0% for OSL ûlms with grain sizes of 50 μm and 200 μm, respectively). The CaF 2 detectors showed a linear dose-response (0.5 to 50 mGy) for both low-energy X-ray photon beams (29 to 110 keV) and photons emitted by a source by a 60 Co source (1225 KeV), as well as for beta particles from a 90 Sr/ 90 Y source (2.7 MeV). The optical fading decreased by 50% over 3 days, then the OSL signal remained stability over a period of 1 month. It was established that CaF 2 OSL ûlms produced could be reused after optical treatment with blue LED (470 m) with an intensity of 80 mW/cm 2 in the Risø TL/OSL reader (80 mW/cm 2 ) for 30 minutes or 5 hours when exposed to blue LED (10W lamp) with a resulting intensity of approximately 7 mW/cm 2 at the sample position. Considering the grain sizes of CaF 2 (50 μm and 200 μm) in ûlm production and the evaluated dosimetric properties, ûlms with smaller grain sizes can be used for dose mapping in relatively high energies in the MeV range, such as in radiotherapy. In contrast, ûlms with larger grain sizes present greater sensitivity and can be used for lower doses and energies (keV), such as in diagnostic imaging.